Assessment of the thirst dimension: integrative review - Pamela Rafaela Martins; Lígia Fahl Fonseca (Universidade Federal de Goias, 2017)
Thirst is a multifactorial and subjective symptom that request multiple measuring instruments. The objective of this study was to identify the assessment dimensions of thirst and the measurement tools used. We included studies published between 2005 and 2015 from the databases Lilacs, PubMed and SciELO. Eighteen articles composed the final sample that showed thirst dimensions: intensity, frequency, and discomfort. We also assessed the xerostomia and its intensity. These dimensions were identified by Visual Analogic Scales, Verbal Numeric Scales, Face's Scales and Likert-type Scales, used in the Thirst Inventory, Xerostomia Inventory, and Thirst Discomfort Scale. We assessed thirst especially in dialytic patients and the ones admitted to the intensive care unit. Although thirst is a symptom, in general, its assessment concentrates in its intensity, and it is conducted in specific populations.